Sintesis Codoped-Sr2TiO4 Fasa Ruddlesden-Popper dengan Metoda Lelehan Garam dan Sifat Hantaran Listriknya - Mulia, Elan; Sabrina, Ayu; Aprianti, Dila Kartika; Andriani, Nova; Zulhadjri, Zulhadjri; Putri, Yulia Eka (Jurnal Riset Kimia, 2020)
In this research, undoped-Sr2TiO4 and codoped-Sr2TiO4 Ruddlesden-Popper (RP) phase compounds have been synthesized with mole variations of Sr:Ti and dopants. Double substitution with Sm3+ for Sr2+ sites and Nb5+ for Ti4+ sites forming Sr2-xSmxTi1-yNbyO4 (x = 0.0125; 0.025; 0.05; 0.1 and y = 0.0125) aimed to increase the number of electrons carrier, so that the electrical conductivity enhanced. The XRD patterns showed that the highest purity of prepared Sr2TiO4 RP phase sample was obtained at the mole ratio of Sr:Ti of 2:1 with specific peaks at 2θ: 31.35°, 46.73°, and 57.33°. Then, this mole ratio was used to prepare the codoped-samples, and the XRD patterns showed the Sr1.95Sm0.05Ti0.9875Nb0.0125O4 sample has the highest purity. SEM images showed that the undoped-Sr2TiO4 and codoped-Sr2TiO4 samples have a plate-like particles with micrometer size. The electrical conductivity of Sr1.95Sm0.05Ti0.9875Nb0.0125O4 sample was measured to be a 17-fold increase compared to that of undoped-Sr2TiO4 sample.